Penerapan Instruksi Pada Tahap Conceptualization Pembelajaran Guided Inquiry untuk Meningkatkan Kemampuan Menemukan dan Menghubungkan Konsep - Windi Ria Fransiska; Nurmiyati Nurmiyati; Sri Widoretno (Universitas Sebelas Maret, 2017)
The research aims to improve the ability to find and connect the concepts of students by implementationinstruction in the conceptualization stage of guided inquiry learning. This research is a classroom actionresearch through 2 cycles. The research subject is 32 senior high school students consist of 24 female studentsand 8 male students. The research procedure through stages are planning, action and observation and reflection.Data were collected trough observation, interviews, documentation and tests for measure score of concept map.Validity of the data with triangulation method. Data analysis using data reduction, data presentation anddrawing conclusions based on qualitative descriptive analysis. The results showed the ability to find andconnect the concept based on the concept map score on pre cycle range from 2.32%-10.6%, an average conceptmap score of 4.63% with 15 of students above average score. The cycle 1 identified from score of concept mapis range 5.55%-35.6%, an average concept map score of 11.14% with 7 of students above average score. Thecycle 2 identified from score of concept map is range 7.5%-61.62%, an average concept map score of 19.4%with 10 of students above average score, thus the ability to find and connect concepts based on the range andmean score of the concept map students increased from pre cycle up to cycle 2.